2021
DOI: 10.1093/narcan/zcab009
|View full text |Cite|
|
Sign up to set email alerts
|

Elucidation of the BMI1 interactome identifies novel regulatory roles in glioblastoma

Abstract: Glioblastoma (GBM) is the most common and aggressive intrinsic brain tumour in adults. Epigenetic mechanisms controlling normal brain development are often dysregulated in GBM. Among these, BMI1, a structural component of the Polycomb Repressive Complex 1 (PRC1), which promotes the H2AK119ub catalytic activity of Ring1B, is upregulated in GBM and its tumorigenic role has been shown in vitro and in vivo. Here, we have used protein and chromatin immunoprecipitation followed by mass spectrometry (MS) analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 118 publications
1
1
0
Order By: Relevance
“…Recently, Nayak ( 26 ) reported that nuclear VAV3 served an important role in B-cell lymphoblastic leukemogenesis through regulation of nuclear Bmi1 phosphorylation and polycomb repression complex-1 (PRC1) activity. the role of BMI 1 in the regulation of glioblastoma migration, invasion and stem cell renewal has been reported by numerous previous studies ( 27 30 ). Therefore, VAV3 could regulate glioblastoma migration, invasion and stem cell stemness via regulation of the PI3K-AKT signaling pathway or PRC1 activity.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, Nayak ( 26 ) reported that nuclear VAV3 served an important role in B-cell lymphoblastic leukemogenesis through regulation of nuclear Bmi1 phosphorylation and polycomb repression complex-1 (PRC1) activity. the role of BMI 1 in the regulation of glioblastoma migration, invasion and stem cell renewal has been reported by numerous previous studies ( 27 30 ). Therefore, VAV3 could regulate glioblastoma migration, invasion and stem cell stemness via regulation of the PI3K-AKT signaling pathway or PRC1 activity.…”
Section: Discussionsupporting
confidence: 60%
“…Consistent with these findings, iSREs accumulate large amounts of cholesterol, which is localized not only in the cell membrane associated with increased lipid rafts but also in an extensive network of lipid droplets. BMI1 has previously been implicated in regulating cholesterol homeostasis in glioblastoma cells, however, in these tumor cells BMI1 was considered to be a negative regulator of cholesterol synthesis via an indirect and undefined pathway (Freire-Beneitez, 2021). In contrast, BMI1 appears to act in iSREs as a positive regulator of cholesterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%